Kesetaraan Dan Keadilan Gender Dalam Jabatan Struktural Tahun 2013 - Bondan Prasetio; Purwoko .; Fitriyah . (Journal of Politic and Government Studies, 2014)
The title of this thesis is Equality and Justice Gender In Structural Position: Practice Study of Gender Equality and Justice in the Structural Position Head of Department in the City of Semarang. This background of research because of the emergence of the phenomenon where women served in the department head very slightly from year to year. Head of Department a structural position that can be occupied by women and men and have the same opportunities for structural department head positions. In article 62 of Law No.22/2009 of department is headed by a department head appointed by the regional head (mayor) of the civil servants who meet the above requirement proposed secretary regional. Government Regulation No.100/2000 amended by the Government Regulation No.13/2003 on structural position is a position that shows the duties, responsibilities, powers, and privileges of a civil servant in order to lead an organizational unit of the state. Local regulation No.3/2010 about structural positions mentioned requirement that the placement officer echelons II structure through Fit and proper test. With the existing regulations, women and men have equal opportunities and opportunities. But women still occupy fewer positions department heads. The problem formulation presented in this study is